Barriers to Adoption of Hospital Management Systems : A Study of Punjab Healthcare Industry - Batra, Roopali; Pall, Amanpartap Singh (Prabandhan: Indian Journal of Management, 2016)
The convergence of information technology in healthcare has the potential to revolutionise this sector. Technology integration in the form of hospital management systems popularly known as hospital information systems (HIS) offers a big opportunity not only to enhance service quality, but also reduce healthcare costs and increase patient satisfaction and care. It facilitates integration of hospital processes and management of medical information to foster a culture of efficiency. Nevertheless, in the Indian healthcare sector, as compared to its peer nations, the state of technology integration is dismal, with sluggish adoption of HIS. The state of Punjab is no exception to this. Interestingly, hospitals in Punjab possess advanced medical technology and health care delivery infrastructure, but still, they are trapped in relentless competition, high healthcare costs, and poor patient satisfaction. Numerous barriers exist that refrain the hospitals from implementing HIS. Punjab health challenges, though unique and complex, offer a remarkable opportunity. Our research aimed at specifically identifying the factors that are responsible for the low rate of adoption of hospital management systems in the hospitals of Punjab. It further proposed a suggestive framework to industry practitioners and policy makers to tackle these barriers so as to enhance HIS integration and change the face of the Punjab healthcare industry.